Target-Activated prodrugs (TAPs) for the autoregulated inhibition of MMP12 - Cobos-Correa, Amanda; Stein, Frank; Schultz, Carsten (ACS medicinal chemistry letters, 2012)
We describe a prodrug concept in which the target enzyme MMP12 produces its own inhibitor in a two-step activation procedure. By using an MMP12-specific peptide sequence and a known sulfonamide drug integrated in the backbone, the active inhibitor is released upon enzyme cleavage. In in vitro experiments, we present proof of concept that the activation proceeds with useful kinetics. The approach is highly selective over the closely related MMP8. If applied in vivo in the future, these prodrugs might release the active entity in a highly specific manner only at such sites where enzyme activity resides.